Coherent parameters estimation and coherent performance analysis for distributed aperture coherent radar - Jing SONG; Jian-yun ZHANG; Wen-gang ZHANG (Tongxin xuebao)
The closed-form CRB (cramer-rao bounds) of the coherent parameters estimation, which include time delay differences and total phase differences, are derived for the distributed aperture coherent radar with general architecture firstly. Then under the assumption that time delay and phase synchronization errors are all existing, the performance bound of oSNRg (output signal-to-noise ratio gain) is developed based on the aforementioned CRB (Cramer-rao bounds). It is concluded that: the CRB of total phase differences is independent on the carrier frequency and effective bandwidth. More transmitters give higher oSNRg. However, as the number of receivers increase, the oSNRg gradually improve with the input SNR being high sufficiently, and worsen with the input SNR being low. Finally, the numerical examples dem-onstrate the validity of the theoretical results.